Rethinking Participatory Forest Management in Tanzania - Eliezeri Sungusia; Jens Friis Lund; Christian Pilegaard Hansen; Numan Amanzi; Yonika M. Ngaga; Gimbage Mbeyale; Thorsten Treue; Henrik Meilby (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2020)
Around 20 years ago, Tanzania adopted the policy of participatory forest management (PFM) to create incentives for increasing villagers' participation in forest management. The timing is thus fitting to reflect on the achievements and challenges of the PFM process so far. There have certainly been successes. Nonetheless, challenges remain. Notably, there is a mismatch between participation ideals and the way the process has been framed, or structured, as well as outcomes on the ground in terms of actual participation and forest management practices. This working paper presents experiences with PFM from a handful of sites across the country, relying on existing published literature as well as our own research experiences. Having been involved in a number of major PFM research projects in Tanzania, we, the authors, have a combined experience of more than 20 years of conducting research in this field. We summarize important findings that explain the observed chasm between participation ideals and local realities and offer some recommendations. While some of our diagnoses and recommendations may contradict conventional wisdom in forestry, we believe that this report contributes valuable insights to the continued efforts to further sustainable forestry in Tanzania. We begin by outlining the global ideals of participatory forestry. We then present an overview of the realities of PFM as they appear in existing research. We do not attempt an exhaustive survey of literature or our own research. Rather, we emphasize issues concerning the framing of PFM as a bureaucratic and scientific project, and how that shapes it in practice. We then present case studies illustrating some of the core problems with PFM before concluding with some general recommendations for improving participatory forestry policy and guidelines.
Keywords: Q15; Q23; O13; O21; 330; Forestry; Planning; Participation; Inventory; Tenure; CBFM; PFM; Africa; Tanzania; Forstwirtschaft; Kooperative Führung; Theorie-Praxis-Verhältnis; Tansania